Biodiesel production from soybean, corn, sunflower and canola oil by transesterification: a systematic review (Research, Society and Development, 2022)
This study aims to analyze and obtain information from articles published between the years 2017 and 2021, which deal with the production of biodiesel from soybean, corn, sunflower and canola oil through the transesterification process. To this end, a Systematic Literature Review was developed, in which a search for articles on this topic was conducted in five databases: IEEE, Scielo, Science Direct, Scopus, and Web of Science. Based on the search string, 3370 articles were found, and these were submitted to the StArt software, where inclusion and exclusion criteria were established. However, after completing all the steps of selection and analysis of these articles, 29 papers were selected. From these 29 articles, a table containing information about them was made, where it was possible to observe the methodologies employed, as well as the results, thus allowing an analysis of factors that interfere in the production of biodiesel.